Fertility and Structural Change in Hungary - Zsolt Sped́er (Hungarian Demographic Research Institute, 2002)
Today it is a commonly accepted fact that besides fundamental economic and social transformations in the 1990s in Hungary, other, equally far-reaching changes occurred in several domains of life. The same applies to demographic processes, or more specifically to phenomena related to family formation as nuptiality or fertility rates. The present study reveals the findings of a research focusing on lesser known and rarely analysed social factors of childbearing. It is well established that fertility rates declined radically in Hungary between 1990 and 2000. It is also known that the phenomenon is not without European parallels and demographic research has revealed many of the factors behind (Lesthaeghe-Moors 2000; Kamaraś 2001; Philipov-Kohler 2001). These efforts have been instrumental in demonstrating that the major factors explaining the decline are the increase in the typical childbearing age and, to a lower extent, the rising rate of extramarital fertility. Demographic literature talks about a change of patterns when documenting these processes. Giving birth at a younger age, a practice prevalent in ex-Communist countries has been replaced by family formation in later age groups. But is this the whole story? Does this supposedly new mode of behaviour apply equally to all groups? Has the decline in fertility assumed the same pattern in all social strata, in the lower, middle and upper layers? Or are there certain traits that generate different patterns? These are some of the questions we would like to answer to in our study.
Keywords: 300; Familiensoziologie; Frauen; Familienökonomik; Europa